TESTING SOLAR PANELS ENTERING UZBEKISTAN (American Journal of Technology and Applied Sciences, 2024)
The increase in the demand for electricity in our country and the use of organic fuels for the production of electricity lead to global pollution of the environment. As a result, human life is seriously damaged. Therefore, one of the serious and urgent problems facing humanity is to provide environmentally friendly energy to all types of energy consumers. Therefore, the need for solar panels and collectors is increasing, and the requirements for its quality are also increasing. Currently, it is necessary to develop the basic and conceptual design of the laboratory for testing photoelectric modules, to equip it with more than ten modern measuring devices based on the requirements of international standards. By establishing a solar panel certification system, we will prevent the influx of the aforementioned substandard solar panels.